2001
DOI: 10.1080/15227950151073138
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF Α-Globin GENOTYPE ON THE PATHOPHYSIOLOGY OF SICKLE CELL DISEASE

Abstract: The clinical picture of sickle cell disease is heterogeneous and varies tremendously among patients and in the same patient from time to time. The level of HbF, alpha-genotype, beta-haplotype, age, sex, and the environment are important factors that modify the clinical picture of sickle cell disease. My paper focuses on the effect of alpha-globin genotype on the pathophysiology of sickle cell anemia, HbSC disease, and sickle beta-thalassemia. The data indicate that the coinheritance of alpha-thalassemia result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
3
20
0
1
Order By: Relevance
“…Eighteen of the patients described in this study had 4α genes, four had 3α genes, and none had deletion of 2α genes. As previously described α‐thalassemia with 2α genes deleted seems to be protective of stroke . Twenty‐one of the 22 of our patients are carriers of the β S BEN haplotype, five of whom were homozygous and 16 heterozygous for this haplotype.…”
Section: Discussionsupporting
confidence: 64%
“…Eighteen of the patients described in this study had 4α genes, four had 3α genes, and none had deletion of 2α genes. As previously described α‐thalassemia with 2α genes deleted seems to be protective of stroke . Twenty‐one of the 22 of our patients are carriers of the β S BEN haplotype, five of whom were homozygous and 16 heterozygous for this haplotype.…”
Section: Discussionsupporting
confidence: 64%
“…Coinheritance of alpha thalassemia in SCA is characterized by a relative paucity of alpha globin chains, which is believed to result in lower intracellular HbS concentrations, less sickling, and reduced hemolysis . An association between alpha thalassemia trait with higher hemoglobin concentrations and lower reticulocytes has been reported in older children and adults with SCA .…”
Section: Discussionmentioning
confidence: 99%
“…Additional genetic polymorphisms with an established influence on the SCA phenotype have been identified, including coinheritance of alpha thalassemia trait, beta globin haplotype, HbF modifiers ( XmnI , BCL11A , and HBS1L‐MYB polymorphisms), UGT1A1 promoter polymorphisms, and G6PD deficiency. Alpha thalassemia is thought to modulate the SCA phenotype by lowering intracellular hemoglobin concentration, thereby reducing HbS polymerization and decreasing hemolysis . However, the net effect of producing more red blood cells may also increase the incidence of certain vaso‐occlusive events Five major beta globin haplotypes are recognized, named for the country or region of discovery: Senegal (SEN), Benin (BEN), Central African Republic (CAR), Arab‐Indian (AI), and Cameroon (CAM) , as well as noncanonical atypical (ATYP) haplotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical and hematological manifestations of sickle cell anemia (SCA) have been found to be altered by the presence of α- and β-thals [13, 14]. Moreover, several studies have shown that the coexistence of α-thal with SCA can produce consequences that are beneficial in some complications but detrimental in others [15]. As an example, a concurrent α-thal has been shown to reduce the concentration of Hb S and Hb S polymerization in patients with SCA [16].…”
Section: Introductionmentioning
confidence: 99%